196k views
0 votes
-2x^2+6x+1=-3x^2 solve to the nearest tenth

User Sivanraj M
by
4.7k points

1 Answer

5 votes

Explanation:

The given equation is :


-2x^2+6x+1=-3x^2

Taking all the terms to one side of the equation i.e.


-2x^2+6x+1+3x^2=0\\\\x^2+6x+1=0

It is a quadratic equation of the form
ax^2+bx+c=0 whose solution is given by :


x=(-b\pm √(b^2-4ac))/(2a)

Here, a = 1, b = 6 and c = 1

Put all the values,


x=(-6\pm √(6^2-4(1)(1)))/(2(1))\\\\x=-0.171\ and\ x=-5.82

Hence, this is the required solution.

User Hover Ruan
by
5.2k points